Optical characterization of the CdZn(S1–x Sex )2 thin films deposited by spray pyrolysis method - Ilican, Saliha; Zor, Muhsin; Caglar, Yasemin; Caglar, Mujdat (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
CdZn(S1–xSex )2 thin films have been deposited onto glass substrates by the spray pyrolysis method at a 275°C substrate temperature. The average optical transmittance of all the films was over 65% in the wavelength range 450–800 nm. The optical absorption studies reveal that the transition is direct with band gap energy values between 2.47–3.04 eV. The optical constants such as refractive index, extinction coefficient and dielectric constants have been calculated for these films. The dispersion parameters such as Eo (single-oscillator energy) and Ed (dispersive energy) have been discussed in terms of the Wemple–DiDomenico single-oscillator model. The values obtained by this method are suitable for many scientific studies and technological applications, such as gas sensors, heat mirrors, transparent electrodes, solar cells and piezoelectric devices.
Optica Applicata, Vol. 36, 2006, nr 1, s. 29-37
Keywords: optyka; thin film; spray pyrolysis; optical constants; band gap energy